2012
DOI: 10.5489/cuaj.11291
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic effect of testosterone and phophodiesterase-5 inhibitors in hypogonadal men with erectile dysfunction: A systematic review

Abstract: Testosterone deficiency seems to impair the clinical response to phophodiesterase-5 (PDE-5) inhibitors in patients with erectile dysfunction (ED). In hypogonadal men, testosterone repletion was associated with enhanced sexual function in patients who failed initial treatment with sildenafil or tadalafil. We conducted a systematic review of studies that evaluated combination therapy of testosterone and PDE-5 inhibitors in patients with ED and low, low-normal testosterone levels who failed monotherapy. The studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…57 Combination therapy was shown to be beneficial in hypogonadal men with comorbidities. [58][59][60] Furthermore, a systematic review by Alhathal et al 61 indicated that T treatment in men with low-normal T levels (300 to 400 ng/dL) appeared helpful for patients with ED who did not respond to initial treatment with PDE5 inhibitors alone. In addition, in a previous study, T administration increased sildenafil-induced relaxant response of CC in high fat diet-induced rabbit model of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…57 Combination therapy was shown to be beneficial in hypogonadal men with comorbidities. [58][59][60] Furthermore, a systematic review by Alhathal et al 61 indicated that T treatment in men with low-normal T levels (300 to 400 ng/dL) appeared helpful for patients with ED who did not respond to initial treatment with PDE5 inhibitors alone. In addition, in a previous study, T administration increased sildenafil-induced relaxant response of CC in high fat diet-induced rabbit model of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It can improve erectile function by targeting the NO/cGMP signalling pathway. However, approximately 30% of patients with ED due to low androgen levels failed to achieve satisfactory results after PDE5I treatment (Alhathal, Elshal, & Carrier, ). It indicates that along with the NO/cGMP signalling pathway, there may be other signalling pathways involved in the mechanism of ED caused by androgen deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a multicenter, double-blind, placebocontrolled TADEST study examined 173 patients with low testosterone levels and ED. [26,27] Men who received 1% testosterone along with tadalafil had a significant increase in IIEF scores. [26,27] In addition to restoring sexual function, PDE5 inhibitors have also been shown to enhance the Leydig cell secretory function, increasing sperm function and aiding sperm motility.…”
Section: Avanafilmentioning
confidence: 99%
“…[26,27] Men who received 1% testosterone along with tadalafil had a significant increase in IIEF scores. [26,27] In addition to restoring sexual function, PDE5 inhibitors have also been shown to enhance the Leydig cell secretory function, increasing sperm function and aiding sperm motility. [28] The emerging studies point to the efficacy of combination therapy (testosterone supplementation and PDE5 inhibitor use) over monotherapy in the management of ED, especially in men who have a low testosterone level.…”
Section: Avanafilmentioning
confidence: 99%
See 1 more Smart Citation